Hubungan Kualitas Pelayanan Keperawatan Dengan Kepuasan Pasien Di Ruang Rawat Inap Rsau Dr. Siswanto - Nola Juniati; Vitri Dyah; Anik Suwarni (CV. Melek Literasi Press, 2026)
Background: The quality of nursing services is a crucial element in hospital care that has a direct and measurable impact on patient satisfaction. High levels of satisfaction not only reflect the effectiveness and reliability of the services provided but also strengthen public trust in healthcare institutions. Preliminary observations at RSAU dr. Siswanto Karanganyar indicated a decline in the Bed Occupancy Rate (BOR) to 27.56% in November 2024, which may be associated with patient dissatisfaction, particularly concerning the responsiveness of nursing staff.Purpose: This study aimed to analyze the relationship between the quality of nursing services and patient satisfaction in the inpatient ward of RSAU dr. Siswanto Karanganyar.Method: A quantitative approach with a cross-sectional design was employed. The population consisted of 789 inpatients, from which a sample of 88 respondents was selected using proportionate stratified random sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability and analyzed using the Kendall’s tau-b statistical test.Results: The results showed that most respondents rated the quality of nursing services as “good” (61.4%) and reported being “very satisfied” with the services received (60.2%). Statistical analysis revealed a significant relationship between nursing service quality and patient satisfaction (p = 0.006; r = 0.293), indicating a weak but meaningful correlation. These findings underscore that, although the strength of the relationship is relatively low, improving nursing service quality remains a strategic priority for enhancing patient satisfaction.Conclusion: Recommended actions include strengthening nurse responsiveness, improving effective communication between nurses and patients, and ensuring that patient needs are addressed promptly, accurately, and comprehensively to create an optimal care experience and improve perceptions of hospital service quality.